Overdiagnosis of urinary tract infection linked to overdiagnosis of pneumonia: a multihospital cohort study. Issue 5 (5th January 2022) - Gupta, Ashwin; Petty, Lindsay; Gandhi, Tejal; Flanders, Scott; Hsaiky, Lama; Basu, Tanima; Zhang, Qisu; Horowitz, Jennifer; Masood, Zainab; Chopra, Vineet; Vaughn, Valerie M
Abstract : Urinary tract infection (UTI) and community-acquired pneumonia (CAP) are the most common infections treated in hospitals. UTI and CAP are also commonly overdiagnosed, resulting in unnecessary antibiotic use and diagnostic delays. While much is known individually about overdiagnosis of UTI and CAP, it is not known whether hospitals with higher overdiagnosis of one also have higher overdiagnosis of the other. Correlation of overdiagnosis of these two conditions may indicate underlying hospital-level contributors, which in turn may represent targets for intervention. To evaluate the association of overdiagnosis of UTI and CAP, we first determined the proportion of hospitalised patients treated for CAP or UTI at 46 hospitals in Michigan who were overdiagnosed according to national guideline definitions. Then, we used Pearson's correlation coefficient to compare hospital proportions of overdiagnosis of CAP and UTI. Finally, we assessed for 'diagnostic momentum' (ie, accepting a previous diagnosis without sufficient scepticism) by determining how often overdiagnosed patients remained on antibiotics on day 3 of hospitalisation. We included 14 085 patients treated for CAP (11.4% were overdiagnosed) and 10 398 patients treated for UTI (27.8% were overdiagnosed) across 46 hospitals. Within hospitals, the proportion of patients overdiagnosed with UTI was moderately correlated with the proportion of patients overdiagnosed with CAP (r=0.53, p<0.001). Over 80% (81.8% (n=952/1164) of UTI; 89.9% (n=796/885) of CAP) of overdiagnosed patients started on antibiotics by an emergency medicine clinician remained on antibiotics on day 3 of hospitalisation. In conclusion, we found overdiagnosis of UTI and CAP to be correlated at the hospital level. Reducing overdiagnosis of these two common infections may benefit from systematic interventions.